2022
DOI: 10.1186/s12877-022-02821-1
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative 5-country comparison of the perceived impacts of COVID-19 on people living with dementia and unpaid carers

Abstract: Background Emerging evidence shows an impact of the COVID-19 pandemic on people living with dementia and informal carers, without any evidence-based global comparison to date. The aim of this international study was to explore and compare the perceived impact of COVID-19 and associated public health restrictions on the lives of people living with dementia and informal carers and access to dementia care across five countries. Methods Informal carers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…Finally, it is important to note, similar to other research, 31 that whilst carers and the majority of the people with dementia they supported were happy to engage online during the pandemic due to necessity, there was a strong preference for face-to-face contact in 'normal' times. This finding reaffirms calls from other research for the urgent re-introduction of community services that can facilitate inperson social contact.…”
Section: Supporting Technological Inclusion For Carers Of People With...supporting
confidence: 65%
See 1 more Smart Citation
“…Finally, it is important to note, similar to other research, 31 that whilst carers and the majority of the people with dementia they supported were happy to engage online during the pandemic due to necessity, there was a strong preference for face-to-face contact in 'normal' times. This finding reaffirms calls from other research for the urgent re-introduction of community services that can facilitate inperson social contact.…”
Section: Supporting Technological Inclusion For Carers Of People With...supporting
confidence: 65%
“…The majority of studies examine, more broadly, the experiences of people with dementia and their carers during the pandemic and often note an increase in their use of digital technologies to engage with formal health and social care services. 30 , 31 , 32 , 33 Although Giebel et al 34 found that those unpaid carers and people with dementia that accessed digital support during this period reported these services to be of poorer quality and less effective than in‐person contact. One UK study that explored the use of ICT by people with dementia during the pandemic found they used these mediums to facilitate social connection, engage in hobbies and interests, and assist in activities of daily living; although people with dementia also encountered accessibility challenges due to cognitive fatigue and usability issues with the technology.…”
Section: Introductionmentioning
confidence: 98%
“…Despite these limitations, there are strengths. This study mirrors many other studies that demonstrated worldwide increases in caregiver anxiety, care work, financial difficulty, loneliness, and care work [ 23 , 24 , 25 , 26 , 43 , 78 , 81 , 83 , 84 ]. We used regression analysis and validated scales to examine the factors related to anxiety and then used mediation analysis to test hypotheses about the processes by which giving care can cause anxiety.…”
Section: Discussionsupporting
confidence: 88%
“…Caregiver distress begins to rise significantly for those providing over 21 hours of care per week [ 31 , 32 ]. Weekly care time and care intensity increased substantially at the outset of the COVID-19 pandemic as home care supports and respite were reduced, and day programs closed in order to redirect healthcare resources into acute care and reduce risk of COVID transmission [ 34 , 35 , 78 ]. Caregivers reported that without stimulation and social interaction, the care-receiver’s health deteriorated, which increased their care time and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies asked informal caregivers to describe their perceived changes in psychosocial wellbeing and health ( Rothgang and Wolf-Ostermann, 2020 , Eggert et al., 2020 , Horn and Schweppe, 2020 ). Qualitative studies were conducted as well – however, they also used only convenience samples, restricting the generalizability of the findings (e.g., Geyer et al., 2020 , Giebel et al., 2022 , Lafferty et al., 2022 ). Some studies assessed the outcomes retrospectively before and during the pandemic (e.g., Altieri and Santangelo, 2021 , Brandt et al., 2021 ), although retrospective data collection is prone to recall and reporting bias.…”
Section: Introductionmentioning
confidence: 99%